Environmental hazards and its relationship with falls among older people with low back pain: a systematic review/ Zarina Zahari, Siti Munirah Omar and Maria Justine - Zahari, Zarina; Omar, Siti Munirah; Justine, Maria (Faculty of Health Sciences, Universiti Teknologi MARA, 2020)
This systematic review aimed to identify the environmental hazards and their relationship with falls among older people with low back pain (LBP). The search strategies were performed via Science Direct, PubMed, Scopus, and Google Scholar databases from 1998 to 2019. The keywords "environmental hazards", "fall", "low back pain", "elderly", "older adults", "older persons" and "older people" were used during the literature search. Boolean operators were used to expanding or limiting the searching scope and manual exclusion was performed to choose articles eligible for this study. A total of 2065 articles were retrieved but only six articles were related to environmental hazards and falls among older people with LBP. The finding shows that environmental hazards are the contributing factors to falls among older people with LBP. In conclusion, the environmental hazards lead to an increase in falls among older people with LBP but, it may not be a primary factor of falls among older people.